Innovation and Creative Entrepreneurship Management in Supporting Cultural Tourism at UNESCO World Heritage Sites - Rafinita Aditia; Thomas Kano (International Journal of Social and Political Sciences, 2025)
This study aims is to identify and analyze the innovations applied in creative entrepreneurship to support the management of cultural tourism at Borobudur. The focus is on understanding how creative entrepreneurship can contribute to both the growth of tourism and the preservation of cultural heritage at this iconic site This research employs a qualitative approach, relying on literature studies related to creative entrepreneurship and cultural tourism. Additionally, field observations were conducted to examine the practices of tourism management at the Borobudur site, particularly in relation to cultural events, digital marketing strategies, and sustainable tourism efforts. The study revealed that innovations in digital marketing, the organization of cultural events, and the management of ecotourism play significant roles in attracting tourists while simultaneously preserving cultural values. These innovations have proven effective in enhancing the visitor experience and increasing awareness about the importance of cultural heritage preservation. The findings suggest that entrepreneurial innovations can strengthen the economic sustainability of cultural tourism by actively involving the local community and expanding the reach to international markets. This approach not only drives economic growth but also contributes to the long-term development of the tourism sector, creating a model that can be replicated in other cultural tourism destinations.